Generalisation decrement and not overshadowing by associative competition among pairs of landmarks in a navigation task with humans. Issue 2 (February 2019) - Sansa, Joan; Aznar-Casanova, J Antonio; Rodríguez, Clara A; Chamizo, Victoria D
In three experiments, a virtual preparation for humans of the Morris water task (VMWT) was used. Experiment 1 established that four landmarks were of similar salience. Then, in Experiments 2 and 3, participants were trained to locate a hidden platform in the presence or either two or four of the previous landmarks. In Experiment 2, one pair of groups was trained with four visual landmarks spaced at equal intervals around the edge of the pool, while a second pair was trained with two landmarks only, either relatively close to or far from the hidden platform. After training, a reciprocal overshadowing effect was found: on a test without the platform with two landmarks only (either close to or far from the platform position), the participants trained with four landmarks spent less time in the platform quadrant than those trained with only two. Finally, Experiment 3 showed that at least participants trained with two landmarks relatively close to the platform and then tested with four also performed worse on test than those trained and tested with two close landmarks only. This result suggests that generalisation decrement, rather than associative competition, could provide a sufficient explanation for the overshadowing observed in Experiment 2 in the proximal groups. The present set of experiments extend, although only partially, the generalisation decrement results documented in rats to human participants.